Implementasi Kecerdasan Kinestetik Pada Kegiatan Ekstrakrikuler Bola Voli - Aziz, Donny Khoirul; Musyayadah, Ummul (AR-RIAYAH: Jurnal Pendidikan Dasar, 2019)
This article aims to examine the implementation of kinaesthetic intelligence in the extracurricular volleyball activities in the elementary School of Gentasari 05 in the district of district of Cilacap Regency. It is important to be discussed considering elementary school age is good for the development of motor activity.Â  This research uses qualitative research methods. The objectives of the study included the head of the Skolah, coaches, and students who participated in the extracurricular volleyball activities. The results of the research on the implementation of kinaesthetic intelligence through the activity of the Ecurricular volleyball in elementary school Gentasari 05 District Kroya Kabupaten Cilacap, namely: 1) high interest to participate in the extracurricular volleyball activities. 2) Select the student's ability to play volleyball. 3) Impersonate a movement. 4) Physical movements. 5) Monitor the kinaesthetic ability of volleyball extracurricular activities in students. 6) Analysis of the implementation of kinaesthetic intelligence in the extracurricular volleyball learning